Does investors react in long-term? The case of Malaysian acquisition - Norhamiza Ishak (Taylor & Francis Group, 2020)
This study examines long-run stock performance for acquirers from years 2000 to 2013. Since acquisitions create agency problem and companies in Malaysia exhibit concentrated ownership structures, this study aims to investigate four major objectives which consist of the effects of family control, blockholder activism, board structures and deal characteristics on stock performance of acquirers. In addressing these objectives, the abnormal returns over 36 months are adopted as the proxy for the long-run stock performance, respectively. Moreover, ordinary least squares regression methods are used to examine the effects of the 16 factors on abnormal returns. The results show that Malaysian market can be considered as efficient, as most of the analyses show that the performance of acquirers does not differ from those of the matching firms. The findings imply that managers of family-controlled firms do not have to worry about investors penalizing them, as long as they engage in value-creating acquisitions. Moreover, institutional blockholders should play an active role if they want to protect their investments. Finally, investors have to realize that over the long run, there is no trading strategy that could be adopted to earn abnormal profit.